Accumulation of metals and metalloids in radish (Raphanus sativus L.) and spinach (Spinacea oleracea L.) irrigated with domestic wastewater in the peri-urban areas of Khushab City, Pakistan. Issue 1 (2nd January 2016) - Ahmad, Kafeel; Khan, Zafar Iqbal; Yasmin, Sumaira; Akram, Nudrat Aisha; Ashraf, Muhammad; Ashfaq, Asma; Fardous, Asia
ABSTRACT: Accumulation of different metals and metalloids was assessed in two vegetables radish ( Raphanus sativus L.) and spinach ( Spinacea oleracea L.) irrigated with domestic wastewater in the peri-urban areas of Khushab City, Pakistan. In general, the metal and metalloid concentrations in radish and spinach were higher at site-II treated with sewage water than those found at site-I treated with canal water. In case of radish at both sites the levels of metals (Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Se, Mo, Cd, and Pb) were below the permissible level except those of Mn, Ni, Mo, Cd, and Pb. At both sites, the transfer factor ranged from 0.047–228.3 mg kg −1 with Cr having the highest transfer factor. The metal pollution index in soil was in the following order: As > Fe > Ni > Zn > Cd > Mo > Se > Co > Pb > Mn > Cr > Cu, respectively. While in case of spinach at both sites, the concentrations of metals and metalloids in vegetable samples irrigated with canal and sewage water were observed below the permissible level except Mn, Ni, Zn, Mo, and Pb. At both sites, the transfer factor ranged from 0.038–245.4 mg kg −1 with Cr having the highest transfer factor. The metal pollution index in soil was in the following order: Cd > Ni > Co > Se > Mn > Zn > Mo > Pb > Fe > Cr > As > Cu, respectively.